2013
DOI: 10.1123/ijsnem.23.3.271
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Increasing Levels of High-Density Lipoprotein Cholesterol: A Pilot Study of Combination Aerobic- and Resistance-Exercise Training

Abstract: Evidence suggests that physical activity has a beneficial effect of elevated high-density lipoprotein cholesterol (HDL-C) on reducing coronary artery risk. However, previous studies show contrasting results for this association between different types of exercise training (i.e., aerobic, resistance, or combined aerobic and resistance training). The aim of this study was to determine which type of exercise training is more effective in increasing HDL-C levels. Forty obese men, age 18-29 yr, were randomized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
(41 reference statements)
0
14
0
2
Order By: Relevance
“…[37][38][39][40][41][42][43] However, many of these animal studies employed very intense vibration stimuli for prolonged periods of time, and whether such responses would occur in a medicaltransportation vehicular setting is unknown. In regards to the biological effects of high-frequency vibration and shock, little is understood about the underlying pathophysiologic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43] However, many of these animal studies employed very intense vibration stimuli for prolonged periods of time, and whether such responses would occur in a medicaltransportation vehicular setting is unknown. In regards to the biological effects of high-frequency vibration and shock, little is understood about the underlying pathophysiologic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the eight trials found concurrent exercise training conferred similar BP benefi ts to those achieved with aerobic and dynamic resistance training alone among young men with prehypertension [ 49 ] and obesity (6-10 mmHg) [ 50 ], older men with hypertension (12-24 mmHg) [ 23 ], and middle-aged adults with prehypertension and obesity (3-5 mmHg) [ 46 ], despite widely varying concurrent exercise training programs. In contrast, combined aerobic and resistance exercise performed on separate days did not reduce BP among middle-aged men [ 56 ] and women [ 57 ] with prehypertension; similar fi ndings were reported following concurrent exercise training (i.e., on the same day ) among middle-aged women [ 55 ] and older adults with pre-to-established hypertension [ 58 ] (see Table 3.2 ).…”
Section: Exercise Modality and Blood Pressure: Aerobic Versus Resistamentioning
confidence: 97%
“…Tseng and co-investigators [ 50 ] had 40 young men with normal BP to prehypertension and obesity (~30 kg/m 2 ) perform ~45 min of moderate to vigorous intensity aerobic, resistance, or combined exercise training (aerobic and resistance exercise performed on separate days ), 5 days weekly for 12 weeks (see Table 3.2 ). Tseng et al found that resting BP was reduced by ~4-8 mmHg compared to baseline ( p < 0.001), and these reductions were similar following aerobic (6-8 mmHg), resistance (4-5 mmHg), and concurrent exercise training (6-7 mmHg, p > 0.05).…”
Section: Exercise Modality and Blood Pressure: Aerobic Versus Resistamentioning
confidence: 99%
“…HDL Cholesterol levels have been found to be more sensitive to aerobic exercise than other lipid fractions [11]. The impact on HDL cholesterol may also differ by exercise type [12].…”
Section: Introductionmentioning
confidence: 99%